Factors Predicting Total Free Flap Loss after Microsurgical Reconstruction Following the Radical Ablation of Head and Neck Cancers. (17th July 2012) - Fujioka, Masaki
Abstract : Background . With greater experience in microsurgical reconstruction, free tissue transfer has become common and reliable. However, total flap necrosis after microsurgical reconstruction is sometimes seen in patients who have undergone radical ablation of head and neck malignancies. We investigated factors predicting free flap loss in head and neck reconstruction. Methods . We reviewed the records of 111 free flap reconstructions carried out among 107 patients with head and neck cancer who required radical resection and microsurgical reconstruction in our unit from 2004 through 2010. Among these patients, 6 showed total flap necrosis postoperatively. We investigated the associations between primary or recurrent tumor, type of flaps, chemotherapy, and radiotherapy and flap loss. Results . Five of 20 (25.0%) patients who underwent radiotherapy developed flap necrosis: among the 91 patient who did not undergo radiotherapy, only one (1.1%) developed. Preoperative radiotherapy was statistically identified as the most important risk factor for postoperative flap failure. Conclusions . Patients receiving radiation treatment are more likely to develop total flap failure when they undergo reconstructive surgery with free flaps after tumor ablation, because the combination of endarteritis and chronic ischemia caused by radiation damaged endothelial membrane in the recipient vessels, consequently, thrombosis tends to develop.